Driving Optimal Performance: The Synergy of Paternalistic Leadership, Compensation, and Employee Motivation - Maulydia, Elok; Maksum, Ikhsan; Alwahidin, Alwahidin (Fakultas Ekonomi, UIN Maliki Malang, 2025)
This study aims to analyze the influence of paternalistic leadership and compensation on employee performance, as well as to examine the role of motivation as an intervening variable at CV Langgeng Dumadi, a company engaged in construction services and wooden pallet production. A quantitative approach was employed using an explanatory research design. Data were collected through questionnaires from 66 respondents, and analyzed using SmartPLS software with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The analysis involved construct validity and reliability testing (outer model), evaluation of relationships among variables (inner model), and direct and indirect hypothesis testing. The results indicate that both paternalistic leadership and compensation have a positive and significant effect on employee performance. However, motivation was not found to be a significant intervening variable in these relationships. The implications of these findings suggest that organizations should focus directly on strengthening supportive leadership styles and implementing fair and structured compensation systems to effectively enhance employee performance. This study provides practical insights for companies in developing more effective and human-centered managerial policies.